Postmortem Vitreous Humor Magnesium Does Not Elevate in Salt Water Drowning When the Immersion Time Is Less Than an Hour. (December 2017) - Tse, Rexson; Kuo, Ta-Chen; Kesha, Kilak; Garland, Jack; Garland, Sarah; Anne, Sravan; Elstub, Hannah; Cala, Allan
Abstract : Background: Elevation in postmortem vitreous humor sodium and chloride (PMVSC) in salt water drowning (SWD) when the immersion time is less than 1 hour (SWD1) is hypothesized to result from electrolyte changes in blood from salt water inhalation/ingestion during drowning. After approximately 1 hour after death, electrolytes may diffuse into the vitreous humor via the eye coverings. Another abundant element in salt water is magnesium, which is approximately 50 times higher in concentration than the blood and vitreous humor magnesium levels. Magnesium is able to diffuse across the eye coverings but not as easily through the blood-ocular barrier. With these properties, we hypothesize that postmortem vitreous magnesium (PMVM) would not be elevated in SWD1 but become elevated in SWD with immersion times greater than 1 hour (SWD>1). Aim: The aim of this article was to investigate the differences in PMVM and PMVSC between nonimmersion deaths, SWD1, and SWD>1. Methods: This is a 1-year retrospective study comparing PMVM and PMVSC in nonimmersion deaths, SWD1, and SWD>1. Results: Postmortem vitreous magnesium is significantly higher in SWD>1 than SWD1 and nonimmersion deaths, with no significant difference between SWD1 and nonimmersion deaths. Postmortem vitreous humor sodium chloride is statistically higher in SWD1 and SWD>1 than nonimmersion deaths. Conclusions: As a conclusion, PMVSC elevates and PMVM does not elevate in SWD1.